Stepping into the Spotlight: Collaborative Efforts towards Musical Inclusion - Daphne Rickson (Approaches: Music Therapy & Special Music Education, 2014)
This article presents findings from qualitative research which aimed to capture the experience and views of people who were supporting fourteen learners with intellectual disabilities (aged 12-18) to perform with a professional orchestra. Findings have been analysed in two stages. The first analysis, published elsewhere (Rickson 2012), focused on supporters’ experiences of organising and preparing for the performance. The supporters believed that through practising and performing an orchestral work the diverse musicians had the potential to challenge stereotyped portrayals of disability, change attitudes and foster the ongoing inclusion of people with diverse abilities. However, while the learners’ responses during preparatory workshops were described as interesting, meaningful and creative, there seemed to be a general perception that they were vulnerable and in need of protection from potentially unsympathetic audiences. This dichotomy was examined in post-performance interviews with supporters and audience members. Findings, presented here, show that the narrative of vulnerability and ‘overcoming’ persisted. Nevertheless, interviewees remained convinced of the artistic value of the work and believed the learners had the potential to attract wider audiences to their performances. Further opportunities for young people with intellectual disabilities to be involved in community arts projects alongside non-disabled musicians may result.